KEARIFAN LOKAL MASYARAKAT DESA SIALANG JAYA DALAM TRADISI LUBUK LARANGAN DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Annisa Rosdah; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the village of Sialang Jaya Subdistrict of Rambah Rokan Hulu Regency with problems, that (1) How the process of the formation of local wisdom Down the prohibition in the village of Sialang Jaya? (2) what is the value and meaning of the tradition of harvesting fish in the bottom of the ban (lubuk larangan)? The purpose of this research is to explain the process of the formation of local wisdom at the bottom of the prohibition in the village of Sialang Jaya and knowing the value and meaning of the tradition of harvesting fish in the bottom of the prohibition (lubuk larangan). This research is qualitative research, subjects in this research is a key informant who knows or mencetus ideas about the bottom of the ban as Head of customs, Administrators and community leaders Down the ban. As for the objects in this study is taken by using purposive sampling technique in which communities that serve as informants are those who know the history and traditions of the bottom of the prohibition (lubuk larangan). To collect data for researchers use interview and documentation. The results illustrate that the Community tradition of the bottom of the prohibition (lubuk larangan) of Sialang Jaya the ban as an attempt to restore the condition of polluted rivers that start in the village they are caused due to the increasing number of inhabitants who settled along river of Kaiti. The society has its own way of Sialang Jaya in the management of the river forming the bottom with river of Kaiti prohibition, regulations or the existence of a prevailing myth, maintenance by means of mutual (horja) and the use of traditional capture the moment of harvesting. In addition, there are the value and meaning of the tradition is the bottom of the ban as the value of togetherness, of family, mutual, pillars/unity and values compliance. While the meaning of the existence of the bottom of the ban which the establishment of a good communication between the community and as a form of cultural preservation.Keywords: Local Wisdom, Bottom of the Prohibition, Tradition.